Occupational Health During the Covid-19 Pandemic - Nany Hairunisa (Fakultas Kedokteran Universitas Trisakti, 2022)
Despite the significant global burden of COVID-19, the current pandemic has resulted in unprecedented economic hardship. When various business fields are trying to reopen during the present coronavirus disease (COVID-19) pandemic, industrial hygiene (IH), occupational health and safety (K3) are being challenged to be able to assess and manage COVID-19 risks in the workplace. In general, many measures have been designed to control workplace hazards; however, efforts to adapt them specifically to prevent infectious disease outbreaks are still limited. All employers should remain alert and informed about changing outbreak conditions, including the spread of the virus in the community and the availability of testing, and implement appropriate infection prevention and control measures. For this reason, the government and employers need to prepare workers to return to work safely and safely with preventive measures to help reduce the transmission of the virus, especially in the workplace.